1981
DOI: 10.1108/eb002378
|View full text |Cite
|
Sign up to set email alerts
|

Appraisals: Changing Directions

Abstract: The article deals with an experience over some three years in changing the role, content, format and procedures of a formal appraisal system in a large, international manufacturing Company. It covers the reasons why change became necessary, the means by which the changes were agreed and implemented and an interim judgement of the effectiveness of the changes. The lessons learned by the specialists are stated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
1986
1986

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Lawler et al (1984) suggest that whilst current thinking about effective human resources management partly explains the widespread use of appraisal systems, growing concern about productivity and the legal issues surrounding race, sex and age discrimination are factors of equal importance. A study of a large international manufacturing company suggested that the reasons for a review of the existing appraisal system was that 'explosive' growth and substantial reorganization 'had placed severe strains on the managerial stock', leading to a decision to 'audit' management development (Lusher and James, 1981).…”
Section: Purposes Of Appraisal Systemsmentioning
confidence: 99%
“…Lawler et al (1984) suggest that whilst current thinking about effective human resources management partly explains the widespread use of appraisal systems, growing concern about productivity and the legal issues surrounding race, sex and age discrimination are factors of equal importance. A study of a large international manufacturing company suggested that the reasons for a review of the existing appraisal system was that 'explosive' growth and substantial reorganization 'had placed severe strains on the managerial stock', leading to a decision to 'audit' management development (Lusher and James, 1981).…”
Section: Purposes Of Appraisal Systemsmentioning
confidence: 99%